2008
DOI: 10.1128/aem.02072-07
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Bacillus anthracis Spores by a Combination of Biocides and Heating under High-Temperature Short-Time Pasteurization Conditions

Abstract: The milk supply is considered a primary route for a bioterrorism attack with Bacillus anthracis spores because typical high-temperature short-time (HTST) pasteurization conditions cannot inactivate spores. In the event of intentional contamination, an effective method to inactivate the spores in milk under HTST processing conditions is needed. This study was undertaken to identify combinations and concentrations of biocides that can inactivate B. anthracis spores at temperatures in the HTST range in less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Hydrogen peroxide is known to be effective against a wide range of microorganisms (Hilgren, Swanson, Diez-Gonzalez, & Cords, 2009;Lin, Moon, Doyle, & McWatters, 2002;Podolak, Elliott, Taylor, Khurana, & Black, 2009;Venkitanarayanan, Zhao, & Doyle, 1999;Xu, Labuza, & Diez-Gonzalez, 2008). Some studies report on the inactivation of bacterial spores by hydrogen peroxide (Hilgren et al, 2009;Podolak et al, 2009;Xu et al, 2008), however, to the authors' best knowledge there is no research that regards the inactivation of heat resistant molds that may contaminate paperboard materials used in the aseptic processing.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Hydrogen peroxide is known to be effective against a wide range of microorganisms (Hilgren, Swanson, Diez-Gonzalez, & Cords, 2009;Lin, Moon, Doyle, & McWatters, 2002;Podolak, Elliott, Taylor, Khurana, & Black, 2009;Venkitanarayanan, Zhao, & Doyle, 1999;Xu, Labuza, & Diez-Gonzalez, 2008). Some studies report on the inactivation of bacterial spores by hydrogen peroxide (Hilgren et al, 2009;Podolak et al, 2009;Xu et al, 2008), however, to the authors' best knowledge there is no research that regards the inactivation of heat resistant molds that may contaminate paperboard materials used in the aseptic processing.…”
Section: Introductionmentioning
confidence: 92%
“…Some studies report on the inactivation of bacterial spores by hydrogen peroxide (Hilgren et al, 2009;Podolak et al, 2009;Xu et al, 2008), however, to the authors' best knowledge there is no research that regards the inactivation of heat resistant molds that may contaminate paperboard materials used in the aseptic processing. Heat-resistant molds such as Byssochlamys, Neosartorya, Talaromyces, Eupenicillium and anamorph with asexual spores such as Paecilomyces are well-known because of their high heat and chemical resistances (Salomão, Massaguer, & Aragão, 2008;Sant'Ana, Rosenthal, & Massaguer, 2009;Tournas, 1994;Tribst, Franchi, Cristianini, & Massaguer, 2009), involvement in food spoilage (Beuchat & Pitt, 2001;Tribst et al, 2009) and ability to produce mycotoxins (Beuchat & Pitt, 2001;Sant'Ana et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…For example, Xu et al inactivated Bacillus anthracis spores effectively in milk by a combination of heat and hydrogen peroxide [21], while Urakami and coworkers successfully combined ozone treatment with UV irradiation [22]. In addition, joint effects of heat and hydrostatic pressure for complete destruction of Bacillus species spores were observed.…”
Section: Inactivation As Kinetic Process 399mentioning
confidence: 99%
“…Among them, the antimicrobial treatment of indoor air using a thermal heating process is considered safe, effective, and environment-friendly; it does not produce secondary byproducts such as ozone or ions. Some studies on heat treatment have targeted airborne bacterial spores, which are widely used as surrogates for biological warfare agents (Decker, Citek, Harstad, Gross, & Piper, 1954;Grant, Hitchings, McCartney, Ferguson, & Rowe, 2002;Mullican, Buchanan, & Hoffman, 1971;Xu, Labuza, & Diez-Gonzalez, 2008), whereas others have focused on environmental parameters for the culture and survival of vegetative cells (Ehrlich, Miller, & Walker, 1970;Fine & Gervais, 2005;Theunissen, Toom, Burggraaf, Stoiz, & Michel, 1993). Our recent studies showed that a high-temperature, short-time (HTST) process, a type of thermal heating process, can effectively inactivate fungal and bacterial bioaerosols in a continuous-flow system (Jung, Lee, & Kim, 2009a;.…”
Section: Introductionmentioning
confidence: 98%